(untitled) (Revista Latino-Americana de Enfermagem, 2023)
Objective: to analyze the effectiveness of digital self-care in the management of pain and functional disability among people with spine musculoskeletal disorders. Method: a systematic literature review, developed with the PRISMA checklist, of randomized clinical trials of people with spine musculoskeletal disorders and digital interventions accessed by means of computers, smartphones or other portable devices. Databases researched: National Library of Medicine, Excerpta Médica dataBASE, SciVerse Scopus, Literatura Latino-Americana e do Caribe em Ciências da Saúde, Science Citation Indexes, Cumulative Index to Nursing and Allied Health Literature and Physiotherapy Evidence Database. The descriptive synthesis of the results and by means of meta-analyses (fixed-effects model) was performed with the Review Manager software. The methodological quality was evaluated with the Physiotherapy Evidence Database scale. Results: a total of 25 trials were selected (5,142 participants), which showed statistically significant improvements (p <0.05) in 54% (12/22) in the pain levels and 47% (10/21) in functional disability in the Intervention Group. The meta-analyses showed moderate effects on pain intensity and small effects on functional disability. There was a predominance of medium quality studies. Conclusion: the digital care interventions showed a beneficial result in pain intensity and in functional disability, mainly for chronic low back pain. Digital care emerges as promising to support self-management of the spine musculoskeletal conditions. PROSPERO registry number CRD42021282102.